Concentration in the South African equity market and its implied restrictions on the long only equity fund manager's opportunity set - H. Raubenheimer (South African Journal of Business Management, 2010)
South Afric's Equity market provides a large (in terms of volume) but concentrated investment environment. Domestic pension funds are restricted from diversifying globally and are thus faced with a restricted set of investment opportunities. This article describes and quantifies the extent of the concentration on the JSE historically and at present. The article describes the consequent limitations on long-only equity portfolio construction and the implications for the domestic long-only fund manager subject to various active weight limits. The analysis shows that the higher the allowable active bet sizes, the less consistently asset managers are able to implement their views and the less symmetric their response to forecasted excess returns can be. Consequently, the less competitive a long-only fund manager can be alongside hedge funds and similarly constrained long-short managers.
Keywords: 650